The gut microbiome in diabetic patients with hepatocellular carcinoma: distinct bacterial compositional shifts after hepatitis C virus eradication - Ramadan, Mohammed; Amin, Ibrahim A.; Ali, Mohamed E.; Abdelbary, Eman R.; Hetta, Helal F.; Alatawy, Roba; Alanazi, Fawaz E.; Alattar, Abdullah; Alshaman, Reem; Alatawi, Yasser; Salah, Mohammed (Frontiers in Microbiology, 2026)
BackgroundHepatocellular carcinoma (HCC) poses a major global health burden, and diabetic patients remain at high risk even after achieving a sustained virological response (SVR) to hepatitis C virus (HCV) with direct-acting antivirals (DAAs). Gut microbiome dysbiosis is implicated in this heightened risk, but the microbial characteristics and underlying mechanisms remain poorly understood.MethodsWe conducted a cross-sectional study of 81 adults divided into three groups (n = 27 each): (1) diabetic patients with HCC after SVR (DHCC), (2) diabetic patients without HCC after SVR, and (3) healthy controls. Stool samples and clinical data were collected approximately 3 years post-SVR. Microbial diversity, taxonomic composition, and predicted metabolic functions were analyzed and correlated with clinical markers of liver disease.ResultsDHCC patients exhibited marked microbial dysbiosis, including reduced alpha diversity (Chao1, p = 0.003) and significant ecological disruption (Kruskal–Wallis, p < 0.001). The key features included enrichment of Treponema_2 (log₂FC = 7.71, padj < 0.001) and Klebsiella (AUC = 0.88) and depletion of the butyrate-producing genus Faecalibacterium (2.08% vs. 9.99% in controls, p = 0.006). Functional analysis revealed a 56% reduction in butyrate synthesis and a 3.2-fold increase in lipopolysaccharide biosynthesis. These shifts correlated with clinical severity: Treponema_2 abundance was associated with hepatic encephalopathy and AST levels, whereas reduced butyrate inversely correlated with FIB-4 scores. Random forest modeling identified Klebsiella, Enterobacter, and Megasphaera as the top predictors of DHCC.ConclusionDiabetic patients with HCC after HCV eradication exhibit a persistent gut microbiome signature characterized by proinflammatory and carcinogenic features. These findings highlight potential targets for microbiome-based risk stratification and therapeutic interventions in this high-risk population.